Kid stakes - Lawler, Ray (Currency Press, 2015)
A joyful portrait of the summer of the first doll, in which a chance encounter brings Olive and Emma, Roo and Barney, into the shabby Carlton terrace to begin a seventeen year journey of seasonal love and argument. Kid Stakes introduces the fun-loving Nancy, who has left the scene by the seventeenth summer, adding a new poignancy to the story.